Role of the Bridging Group in Bis‐Pyridyl Ligands: Enhancing Both the Photo‐ and Electroluminescent Features of Cationic (IPr)CuI Complexes. Issue 64 (25th October 2017) - Elie, Margaux; Weber, Michael D.; Di Meo, Florent; Sguerra, Fabien; Lohier, Jean‐François; Pansu, Robert B.; Renaud, Jean‐Luc; Hamel, Matthieu; Linares, Mathieu; Costa, Rubén D.; Gaillard, Sylvain
Abstract: We report on the benefits of changing the bridging group X of bis‐pyridyl ligands, that is, Py‐X‐Py where X is NH, CH2, C(CH3 )2, or PPh, on the photo‐ and electroluminescent properties of a new family of luminescent cationic H‐heterocyclic carbene (NHC) copper(I) complexes. A joint experimental and theoretical study demonstrates that the bridging group affects the molecular conformation from a planar‐like structure (X is NH and CH2 ) to a boat‐like structure (X is C(CH3 )2 and PPh), leading to i) four‐fold enhancement of the photoluminescence quantum yield ( ϕ em ) without affecting the thermally activated delayed fluorescence mechanism, and ii) one order of magnitude reduction of the ionic conductivity ( σ ) of thin films. This leads to an overall enhancement of the device efficacy and luminance owing to the increased ϕ em and the use of low applied driving currents. Abstract : Building bridges : The structural and electronic features of bis‐pyridyl ligands on cationic copper(I) complexes of general formula [Cu(IPr)(N^N)][PF6 ] are reported. This study led to novel guidelines for enhancing the photo‐ and electroluminescence features of this emerging family of copper(I) complexes.